Gig economy and precarious employment in professional sport: a systematic literature review of contemporary evidence (2022–2025) - Anisa Sholiha Mia; Bram Sujadesman; Jeki Haryanto (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
The gig economy has reshaped how people work around the world. Stable contracts are being replaced by fragmented, platform-based arrangements that often feel precarious. Professional sport offers a really interesting lens for this shift. Athletes, coaches, fitness pros, and match-day staff are increasingly working under insecure conditions mediated by digital platforms. Yet this area hasn't been studied much. So we did a systematic literature review. We wanted to pull together what's already known about gig and precarious employment and figure out how it applies to the sports labor market. The whole thing followed the PRISMA 2020 guidelines. We searched Scopus on January 15, 2025, using a predefined Boolean strategy applied to TITLE-ABS-KEY fields. Two independent reviewers handled screening and eligibility. For methodological quality, we used the FICO framework before moving into thematic synthesis. Out of 886 records found, only 10 studies made it through, all published between 2022 and 2025. The synthesis tackled three big questions: what structural features define precarious employment, how algorithmic management and employment relations work, and what all this means for worker wellbeing, identity, and collective agency. Four main findings stood out. Platform work gives the illusion of autonomy while actually increasing financial dependence. Algorithmic management limits career growth and job security. Precarity takes a real toll on mental health, organizational identification, and hits gendered vulnerabilities hard. And workers show constrained agency through coping strategies and collective action. These insights offer a useful theoretical frame and practical takeaways for sport governance. But they also make it clear we need more longitudinal research that's specific to sport.